Formulation and Antioxidant Activity Test of Purple Button Herb Ethanol Extract Peel-Off Mask - Ifaya, Mus; Baco, Juliana; Lolok, Nikeherpianti; Hasanuddin, Silviana; Rama, Wa; Fitriani, Rezky D. (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Purple button herb (Borreria laevis Lamk) contains secondary metabolites, including flavonoids, saponins, phenolics, tannins, and steroids, which have antioxidant activity. Facial masks include pharmaceutical preparations for cleaning, maintaining, and increasing attractiveness. This study aims to formulate a peel-off facial mask preparation from purple button herb extract (Borreria laevis Lamk), which is good and stable as an antioxidant. Ethanol extract from purple button herb was used as an active ingredient in the manufacture of peel-off gel masks with concentrations of 5% (F1), 10% (F2), and 15% (F3) with several physical evaluations including homogeneity, organoleptic (odor, color, shape), pH, drying time, viscosity and antioxidant activity tests carried out using the DPPH method. The results of the antioxidant activity test showed that the peel-off gel mask formula of ethanol extract of purple button herb at concentrations of 5%, 10%, and 15% met the requirements of a good and stable preparation with an IC50 value at a concentration of 5% (F1) of 149.82 µg/mL in the moderate category for antioxidant activity. Based on the test results, the purple button herb can be an antioxidant formulated for peel-off facial masks.